Cardiovascular disease and malignant melanoma. Issue 3 (29th March 2022) - Wang, Charlie Yue; Zoungas, Sophia; Voskoboynik, Mark; Mar, Victoria
Abstract : In the last decade, systemic therapies such as immune checkpoint inhibitors and BRAF-MEK inhibitors have improved the prognosis of high-risk and advanced melanoma. With improved survival, melanoma survivorship is increasingly important, particularly in patients who have a good prognosis or are diagnosed at a younger age. It is increasingly recognized that cancer and its treatment is associated with increased cardiovascular morbidity and mortality. Indeed, data from observational studies and meta-analyses of randomized controls trials in melanoma show that systemic therapies may be associated with cardiac toxicities, such as myocardial infarction, heart failure, myocarditis and stroke. Our review will discuss cardiovascular disease and risk factors in the context of melanoma and outline the importance of cardiovascular risk modification in this population.